2017
DOI: 10.1186/s12863-017-0504-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel nonsense mutation in the tyrosinase gene is related to the albinism in a capuchin monkey (Sapajus apella)

Abstract: BackgroundOculocutaneous Albinism (OCA) is an autosomal recessive inherited condition that affects the pigmentation of eyes, hair and skin. The OCA phenotype may be caused by mutations in the tyrosinase gene (TYR), which expresses the tyrosinase enzyme and has an important role in the synthesis of melanin pigment. The aim of this study was to identify the genetic mutation responsible for the albinism in a captive capuchin monkey, and to describe the TYR gene of normal phenotype individuals. In addition, we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Albinism happens among different living things varying from human beings, animals as well as higher plants (33)(34)(35). In this study, some albino seedlings were observed in the progenies from a selfpollinated cucumber fruit during the breeding selection period of an inbred line named g32.…”
Section: Discussionmentioning
confidence: 70%
“…Albinism happens among different living things varying from human beings, animals as well as higher plants (33)(34)(35). In this study, some albino seedlings were observed in the progenies from a selfpollinated cucumber fruit during the breeding selection period of an inbred line named g32.…”
Section: Discussionmentioning
confidence: 70%
“…Albinism occurs among different living organisms ranging from human beings to animals as well as higher plants ( Kamaraj and Purohit, 2014 ; Galante Rocha de Vasconcelos et al., 2017 ; Le Ret et al., 2018 ). In the present study, some albino seedlings were observed in the progenies of a self-pollinated cucumber fruit during seed increase period of a cucumber inbred line named “g32”.…”
Section: Discussionmentioning
confidence: 99%
“…Chicken [39][40][41] Ungulates Water buffalo [42], Cattle [43], Red deer [44], Asinara donkey [45] Rodents House mouse [46], Wistar rat [47], Domestic guinea pig [48] Primates Crab-eating macaque [49], Capuchin monkey [50], Hamadryas baboon [51], Human [reviewed in 52]…”
Section: Fishmentioning
confidence: 99%